CATHOLIC REFORMATION RESEARCH IN THE 20TH CENTURY - Schmiedl, Joachim (Asian Horizons, 2017)
The Catholic view of Martin Luther had been marked by polemics for centuries. Approaches to a re-evaluation are only apparent in the 20th century. They are connected with a discovery of Luther’s renewal of the Church by Catholic theologians. A milestone was the study by Joseph Lortz on “The Reformation in Germany” (1939). 1961 controversy triggered, when Erwin Iserloh deconstructed the myth of the fixing of the 95 theses. In the 1970s and 1980s, research focused on the development of religious denominations in the 16th century that led to different forms of life and religious cultures. Today Luther is seen and evaluated in ecumenical perspective in his spiritual dimension. The beginnings of the Reformation are therefore important landmarks for a theological view of Luther and his fundamental concerns, which are common to the Catholic and Protestant Churches.